Analysis of the Impact of Coretax Implementation and Tax Compliance Moderation on Tax Gap Reduction in the Digital Era - Siti Aminah (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study analyzes the impact of Coretax implementation and tax compliance moderation on reducing the tax gap in the digital era. The tax gap, resulting from discrepancies between taxes owed and taxes paid, is increasingly challenging to address in the context of growing digital transactions. The research uses a library-based approach, reviewing literature on digital tax systems and compliance strategies. The findings show that while Coretax systems enhance efficiency, their effectiveness is maximized when combined with behavioral interventions like taxpayer education and trust-building. The study concludes that a holistic approach, integrating technology and behavioral strategies, is essential to effectively reducing the tax gap and improving tax compliance.